(untitled) (INNOVATIVE ECONOMY, 2023)
Demianyshyn V.H., Lobodina Z.M., Kostetskyi V.V., Demianyshyn V.V. DIRECTIONS FOR THE DEVELOPMENT OF INFORMATION TECHNOLOGIES IN THE MANAGEMENT OF PUBLIC FINANCES, STATE FINANCIAL RESOURCES AND FINANCIAL SECURITY OF PUBLIC SECTOR ENTITIES Purpose. The aim of the article is to disclosure the theoretical and practical foundations of the modernization of information technologies in the management of public finances, state financial resources and financial security of public sector economic entities, identification of positive, negative, problematic aspects of the study and, based on them, the formulation of the main conceptual approaches, vectors of their development in the conditions of market transformations and integration of Ukraine’s economy into the EU. Methodology of research. In the process of scientific analysis, a number of scientific approaches, general scientific, specifically scientific and special methods were used. The dialectical approach is based on the use of categories and laws of dialectics, the process of using information technologies in the management of public finances. The institutional approach was focused on the study of the relationship between the strategic goals and directions of their implementation in the Strategy for the Digital Development of the State Finance Management System. The comparative approach made it possible to identify similar and different features when explaining the essence of information support in the management of public finances. The system approach made it possible to consider financial resources, financial security as a whole set of individual constituent parts that interact with each other and make up a single whole. The analytical method was used in the review of the literature on the management of state financial resources. The generalization method made it possible to form conclusions and recommendations as a result of the research. Findings. The development of the public finance management system and the strategic foundations of the digital development of digital transformations and the digital system of public finance management, state financial resources and financial security of public sector economic entities, the stages of this development are considered. The interrelationship between the strategic goals and directions of their implementation in the Strategy for implementation of digital development, digital transformations and digitalization of the state finance management system for the period until 2025, as well as the interrelationship between the strategic goals and directions of implementation of the Strategy for the Reform of the State Finance Management System for 2022-2025 years. The structural and logical scheme of state financial resources management and the mechanism of financial security management of public sector economic entities are characterized. The expected results of the implementation of the strategic tasks of reforming the system of digital management of public finances and financial security are proposed. Originality. As a result of the study, the approaches to the interpretation of the essence of financial resources of the public sector, the determination of the management of public financial resources have gained further development. A refined definition of the financial security of public sector economic entities, approaches to the formation of a mechanism for managing the financial security of state financial relations entities are proposed. Practical value. The conclusions and recommendations contained in the article have a theoretical basis and practical significance. Proposals related to the organization of the management of state financial resources and the financial security of public sector economic entities, the use of new modern digital and information technologies in the process of this management can be used in the practical activities of enterprises, organizations, institutions of state and communal ownership. Key words: public sector, financial resources, financial security, economic entities, financial challenges, financial threats, financial risks, digital transformations, information technologies.